Ileal mucosal absorption of bile acid in man: validation of a miniature flux chamber technique. Issue 4 (April 1992) - Hosie, K B; Davie, R J; Panagamuwa, B; Grobler, S; Keighley, M R; Birch, N J
Abstract : A method that allows the quantitative assessment of ileal mucosal cell uptake and transport of bile acids in mucosal biopsy specimens has been validated. Viability of the tissue was confirmed by maintenance of normal cell morphology, wet weight, extracellular space, porosity to polyethylene glycol-900, lactate dehydrogenase release, and transmucosal potential difference. Using 14C-taurocholic acid, absorption was shown to be directional, capable of working against a concentration gradient, reduced by metabolic inhibitors, and sodium dependent. The system showed saturation kinetics with an estimated Km of 10 mumol/l. At a standard substrate concentration of 10 mumol/l ileal mucosal bile acid absorption was compared in patients with colorectal cancer (n = 6), ulcerative colitis (n = 10), and slow transit constipation (n = 8). There was no significant difference in tissue uptake or transport between the three groups.